Pengaruh Jumlah Dan Diameter Lubang Terhadap Kebisingan Silencer Knalpot Mesin Generator Set (Genset) Proferce 6,5 Hp - Adiguna, Panca Prasetya; Sartika, Dewi; Mukhtar, Anas (Virtual of Mechanical Engineering Article, 2019)
The development of technology today is very fast especially in the sector of ease in using a tool to help human activities one of which is generator set, when there is a problem in the needs of electricity use this tool is very helpful. But in the use of this tool produces a noisy sound. Noise is a problem that can interfere with physical health at risk of hearing loss. Various technical efforts are done to reduce noise levels such as changing the number and diameter of the silencer holes that can decrease the sound produced by the generator well. The purpose of this research was to gain the influence of the number and diameter of the silencer hole against the resulting exhaust noise engine. The research was conducted with experiments, a variation of the number of silencer holes amounted to 18, 23, and 28, while the silencer diameter was used 2mm, 3mm, and 5mm. Noise level measurements are conducted at a distance of 1 meter, 2 meters, and 3 meters from Sound source using a sound level meter. Data retrieval is performed every 1-minute interval using the Stopwatch tool. With the results of the number of holes 23 and hole diameter 2mm that can reduce noise well.